Features of the technological process of construction of houses using modular technology - PASTUKHOVA, Susanna; MISHUK, Kateryna; KUZNIETSOV, Vladyslav (Ways to Improve Construction Efficiency, 2025)
The search for ways to accelerate the construction of buildings of both temporary and long-term aspects has been and remains a leading issue in the construction industry of Ukraine, especially given the conditions of martial law, internal displacement of people, destruction of housing, etc. This article reveals the features of modular technology, which is increasingly used in the construction industry. In particular, during the writing of the work, the differences that are distinguished in modular construction in relation to traditional ones were investigated to create a picture of the practicality and relevance of modular construction objects. Also, based on the analyzed historical discourse on the use of modular technologies, the feasibility of their application in our time was characterized and determined, paying special attention to various factors and factors: martial law, destruction of residential premises and buildings, displacement of highly qualified personnel and the population in general, etc. During the study of the features of modular construction, well-known examples of construction solutions, their specificity and implementation aspects were also studied, on the basis of which the prospects for the development of modular construction in our time, the stages of its gradual introduction into the construction industry and use taking into account certain factors or factors were outlined. Based on the analyzed elements of the influence of organizational and technological factors on the construction industry, it was found that traditional construction has exceptionally high indicators of reliability, durability, stability, etc., but at the same time it is inferior to modular construction of buildings and structures in terms of time and resource consumption, environmental impact, as well as in rapid adaptation to the special challenges of today, of a social or natural nature, etc., which makes the use of modular technologies one of the leading phenomena in the construction sector.